Influence of Storage Temperature and Duration of Tomato Leaf Samples on Proline Content - Brake, Mohammad H.; Hamasha, Hassan R.; Migdadi, Hussein M.; Khashroum, Ashraf O.; Al-Gharaibeh, Moath; Qaryouti, Muien M.; AL-Khatib, Mahmoud T. (European Scientific Journal, ESJ, 2017)
In arid and semi-arid countries such as Jordan, shortage in water sources might affect agricultural development and reduces the effectiveness of economic benefits of most crops planted in such areas. Tomato is an important agricultural crop and faces severe drought stress due to climate changes, therefore, measurement of proline accumulation in plant tissues is used as an indicator for drought stress tolerance. This research was conducted at Jarash University Campus in northern Jordan. A field experiment was carried out to investigate the impact of different storage temperature (+4ºC, - 20ºC and -80ºC) and different storage durations (0, 3, 6 and 11 weeks) on proline content in five different Jordanian tomato landraces. Results indicated that the average free proline content for samples tested directly after leaves collection was 7.1 µmol/g. Proline content in leaves stored at +4 ºC for 3, 6, and 11 weeks was 4.8, 1.8, and 1.1µmol/g, respectively, while for -20ºC was 11.8, 7.9, and 9.5 µmol/g for samples stored for 3, 6, 11 weeks respectively. In contrast the highest values for these parameters were obtained from samples stored at -80ºC, the average measured values of free proline content were 9.5, 7.8, and 12.9 µmol/g at 3, 6, and 11 weeks of storage, respectively. Based on the results obtained by this research, it is recommended to measure proline content directly after leaves collection. However, for large number of samples, keeping the samples at -20ºC not longer than six weeks could be a solution. Finally, we highly recommend the development of in-field method for measurement of free proline content.